Expansion and Antitumor Cytotoxicity of T-Cells Are Augmented by Substrate-Bound CCL21 and Intercellular Adhesion Molecule 1 - Adutler-Lieber, Shimrit; Friedman, Nir; Geiger, Benjamin (Frontiers in Immunology, 2018)
Adoptive immunotherapy is based on ex vivo expansion and stimulation of T-cells, followed by their transfer into patients. The need for the ex-vivo culturing step provides opportunities for modulating the properties of transferred T-cells, enhancing their anti-tumor abilities, and increasing their number. Here, we present a synthetic immune niche (SIN) that increases the number and anti-tumor activity of cytotoxic CD8+ T-cells. We first evaluated the effect of various SIN compositions that mimic the physiological microenvironment encountered by T-cells during their activation and expansion in the lymph node. We found that substrates coated with the chemokine CCL21 together with the adhesion molecule ICAM1 significantly increase the number of ovalbumin-specific murine CD8+ T-cells activated by antigen-loaded dendritic cells or activation microbeads. Notably, cells cultured on these substrates also displayed augmented cytotoxic activity towards ovalbumin-expressing melanoma cells, both in culture and in vivo. This increase in specific cytotoxic activity was associated with a major increase in the cellular levels of the killing-mediator granzyme B. Our results suggest that this SIN may be used for generating T-cells with augmented cytotoxic function, for use in cancer immunotherapy.